2009
DOI: 10.1021/jp9051566
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Dynamics of Water within Mesoporous Materials at Different Hydration Levels during Adsorption and Desorption Processes

Abstract: The vibrational dynamics of water within Vycor 7930 under different hydration levels and adsorption and desorption processes has been investigated by Raman measurements. Based on the successfully depressing the background fluorescence of Vycor, a new Gaussian peaking at 3590 cm -1 has been observed in the Raman spectrum of confined water. By comparison with the published Raman data of water within fully filled silicabased pores or reverse micelles, it is confirmed that a small confinement size may conceal the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Simple estimates suggest that they would at best have a small effect on the spectra that would be difficult to discern in a fully hydrated pore such as that considered here. This is supported by experimental measurements 15,23,24 and the number densities (e.g., in the two pores considered here there are only 56 and 86 silanol groups compared to 882 and 818 water OH groups, respectively). However, the electric field exerted by the silanols on the OH groups is included in the determination of the water OH stretching frequencies, with the exception of the case described below where the field due to the entire silica pore is neglected.…”
Section: A Frequency Map and Implementationsupporting
confidence: 77%
See 2 more Smart Citations
“…Simple estimates suggest that they would at best have a small effect on the spectra that would be difficult to discern in a fully hydrated pore such as that considered here. This is supported by experimental measurements 15,23,24 and the number densities (e.g., in the two pores considered here there are only 56 and 86 silanol groups compared to 882 and 818 water OH groups, respectively). However, the electric field exerted by the silanols on the OH groups is included in the determination of the water OH stretching frequencies, with the exception of the case described below where the field due to the entire silica pore is neglected.…”
Section: A Frequency Map and Implementationsupporting
confidence: 77%
“…24,75,76 For example, Huang et al measured the Raman spectrum of H 2 O confined in 6.9 nm diameter Vycor glass and compared it to the bulk water spectrum. 24 They found that the key differences between bulk and confined water are a general blue-shifting of the spectrum along with the appearance of a shoulder on the high-frequency side.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to completely remove the organic pollutants inside the pores, the glass disks were pretreated strictly following the procedure described in Ref. 19. Bulk aqueous solutions of CuBr 2 were obtained by dissolving an appropriate amount of CuBr 2 salt (Sigma, 99.99 wt.%) into de-ionized water.…”
Section: A Sample Preparationmentioning
confidence: 99%
“…However, to date, there have been very few studies of probing connement of water with silica systems of tunable size. [8][9][10][11][12][13] The use of colloidal particles as hard templates is perhaps the oldest strategy for formation of hollow nanostructures and is still widely used today. An extensive amount of research has gone into the development of colloidal particles with the spec-ications needed to act as good templates.…”
Section: Introductionmentioning
confidence: 99%